Climate change and business: historical perspectives - Lopes, Teresa da Silva; Duguid, Paul; Fredona, Robert (Routledge, 2025)
"Climate change is the greatest market failure in world history and thus the most urgent challenge in the world of business for the foreseeable future. This book brings together experts to shed light on the historical impact of business on climate change and of climate change on business. The book shows how corporate responses to climate change emerged out of earlier environmental concerns, regulatory frameworks, and in many cases already established business strategies. Contributors to the book analyse the evolution of business strategies to navigate environmental challenges even before climate crisis was widely recognized as an urgent concern. The historical insights presented by this book will be essential reading for business historians, as well as students, scholars and reflective practitioners with an interest in the environment, political economy, business strategy, and risk management"--